Midwives in Byzantium: An Overview - Giulia Gollo (Estudios Bizantinos, 2022)
This paper aims to draft an overview of what being a midwife in Byzantium meant, according to the literary sources. Midwife in Byzantium appears to be a rather complex and elusive figure to study. This is due to both the scarce references in the sources and the vague definition of midwifery itself in the ancient world. The main fields of activity of Byzantine midwives were three: medical, religious and care. As a first attempt of studying Byzantine midwife all-round, this paper ends by suggesting further research perspectives in order to get a clearer and more complete understanding of such figure.